2017
DOI: 10.3233/isu-170832
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven maternal health literacy promotion and a postscript on its implications

Abstract: Abstract. Scientific discovery and global health policy are moving health literacy promotion and maternal-child health from the fringes of research and public health to the forefront of healthcare reform [Matern Child Health J. 18 (2014), 344-365]. In 2011 the United Nations General Assembly adopted the Shanghai Declaration [Lancet 378 (2011), 566-567]. The Declaration highlights new understanding of the origins of health and disease in early development. It calls on all nations to apply this knowledge to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Low health literacy in adolescents is associated with a range of adverse health outcomes including health-compromising behaviours, poor health status and overweight/obesity [6][7][8]. Adolescent health literacy is an important and modifiable determinant of health; promoting health literacy at an early age is a key intervention strategy to reduce disease burden and health disparities [9].…”
Section: Introductionmentioning
confidence: 99%
“…Low health literacy in adolescents is associated with a range of adverse health outcomes including health-compromising behaviours, poor health status and overweight/obesity [6][7][8]. Adolescent health literacy is an important and modifiable determinant of health; promoting health literacy at an early age is a key intervention strategy to reduce disease burden and health disparities [9].…”
Section: Introductionmentioning
confidence: 99%
“…33 Mothers play an important role in younger adolescents' development, especially among daughters; 34 as a result, maternal health literacy can empower women to address factors that affect outcomes for both mothers and children. [35][36][37] Although the MHL is considered an important determinant of mental health and has the potential to benefit both the individual and the public, 15,16 its use in evidencebased practices and health promotion interventions has been limited. 38 O'Connor et al 39 conducted an extensive literature review and reported that most of the related investigations had not adequately addressed the psychometric properties of the measuring instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy comprises factors that determine the motivation and ability of people to gain access to, understand, communicate about, and use information in ways that promote and maintain good health (Berkman, Davis, & McCormack, 2010; Nutbeam, 1998). Health literacy research has largely focused on quantitative measures of health literacy in the context of disease treatment and health care (Smith & Carroll, 2017), often focusing on functional health literacy skills such as reading and numerical comprehension (Baker, Williams, Parker, Gazmararian, & Nurss, 1999; Chew, Bradley, & Boyko, 2004; Davis et al, 1991; Parker, Baker, Williams, & Nurss, 1995). This individual function-focused approach does not fully reflect the way that people experience health care, manage health conditions, and make decisions about their health, as it obscures social and cultural context (de Wit et al, 2017).…”
mentioning
confidence: 99%
“…Maternal health literacy broadens the definition of health literacy from promoting and maintaining good health in the individual to promoting and maintaining good health of both the mother and child (Renkert & Nutbeam, 2001). It is associated with children's nutritional (Johri et al, 2016) and vaccination status (Johri et al, 2015) and it has been posited that significant, rapid improvement in maternal health literacy is achievable with appropriate and targeted interventions (Mobley et al, 2014; Smith & Carroll, 2017), even when reading and other functional skills are weak (Smith & Carroll, 2017). Improved maternal health literacy can empower women to address factors that affect outcomes for both mothers and children (Lu & Halfon, 2003; Mobley et al, 2014; Smith & Carroll, 2017).…”
mentioning
confidence: 99%